2012
DOI: 10.1016/j.nlm.2012.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal striatal dopamine depletion impairs both allocentric and egocentric navigation in rats

Abstract: Successful navigation requires interactions among multiple but overlapping neural pathways mediating distinct capabilities, including egocentric (self-oriented, route-based) and allocentric (spatial, map-based) learning. Route-based navigation has been shown to be impaired following acute exposure to the dopaminergic (DA) drugs (+)-methamphetamine and (+)-amphetamine, but not the serotoninergic (5-HT) drugs (±)-3,4-methylenedioxymethamphetamine or (±)-fenfluramine. The dopaminergic-rich neostriatum is involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 49 publications
7
45
1
Order By: Relevance
“…Comparing our data with the data of Ferro et al (2005) and Braun et al (2012) (Table 2) pretreatment with desipramine in our study in contrast to the latter may explain the discrepancy, as a recent study in bilateral 6-OHDA-lesioned mice demonstrated a decreased noradrenaline level in the striatum and the hippocampus without giving desipramine before 6-OHDA injection, but no difference compared to control when desipramine was applied before the lesion (Bonito-Oliva et al, 2013). Other neurotransmitters such as noradrenaline may play an important role in regard to cognitive function in a mouse model of bilateral 6-OHDA lesion.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 53%
See 1 more Smart Citation
“…Comparing our data with the data of Ferro et al (2005) and Braun et al (2012) (Table 2) pretreatment with desipramine in our study in contrast to the latter may explain the discrepancy, as a recent study in bilateral 6-OHDA-lesioned mice demonstrated a decreased noradrenaline level in the striatum and the hippocampus without giving desipramine before 6-OHDA injection, but no difference compared to control when desipramine was applied before the lesion (Bonito-Oliva et al, 2013). Other neurotransmitters such as noradrenaline may play an important role in regard to cognitive function in a mouse model of bilateral 6-OHDA lesion.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 53%
“…In the Morris water maze, animals need to find a hidden platform underneath the water via visuo-spatial cues (Garthe and showing no spatial memory deficits and no difference compared to control (Branchi et al, 2008;Castro et al, 2013). In contrast, some studies reported memory deficits after a 6-OHDA lesion, by increasing latency (Braun et al, 2012;Ferro et al, 2005;Tadaiesky et al, 2008) or tracklength (Braun et al, 2012) to find the hidden platform.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…4D). Given that dopamine depletion contributes to age-related memory decline in human 9,14 and poor performance of MWM tasks, 15 the memory improvement after CMLc supplementation could be a result of improved dopamine function. More recently, we have reported the dopamine depletion and its role in contributing to age-related memory loss in much older (35-36 months old) Fisher/Brown rats.…”
Section: Discussionmentioning
confidence: 99%
“…This acts as a determinant for the successful execution of SWM because the dorsal striatum is involved in the formation and storage of spatial associations of references known as egocentric and allocentric spatial navigation (Braun et al, 2012). DA has an intrinsic participation in both the dorsal striatum and the PFC, which are connected by a circuit through a direct excitatory loop and an indirect inhibitory loop, which, together, are known as the frontostriatal circuit (Alexander et al, 1986;Yeterian and Pandya, 1991).…”
Section: Idiopathicmentioning
confidence: 99%